2023
DOI: 10.3390/cancers15020553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Significances of FBLN5 in Gastric Cancer

Abstract: Abnormal FBLN5 expression levels are related to various cancer types. This study is the first to explore its clinical and biological significances in gastric cancer (GC). We used The Cancer Genome Atlas-GC (TCGA-GC) and Gene Expression Omnibus (GEO) databases to identify the differential expression of FBLN5, and its association with clinical pathological characteristics was analyzed. A Kaplan–Meier plotter was used to calculate the impact of FBLN5 on GC patient prognosis, and the biological functions of FBLN5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among these 6 genes, FBLN7, NPY1R, VTN and EPHB3 have previously been reported to be involved in GC tumor development [16][17][18][19]. X Bian et al also reported that the co-family member FBLN7 was one of the independent risk factors related to GC patient prognosis [27]. Additionally, EPHB2 was reported to be associated with intestinal phenotype of gastric cancer and indicates better prognosis by suppressing gastric cancer migration [28].…”
Section: Discussionmentioning
confidence: 99%
“…Among these 6 genes, FBLN7, NPY1R, VTN and EPHB3 have previously been reported to be involved in GC tumor development [16][17][18][19]. X Bian et al also reported that the co-family member FBLN7 was one of the independent risk factors related to GC patient prognosis [27]. Additionally, EPHB2 was reported to be associated with intestinal phenotype of gastric cancer and indicates better prognosis by suppressing gastric cancer migration [28].…”
Section: Discussionmentioning
confidence: 99%
“… 21 And Sangerbox 22 was utilized to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of these functional protein association networks. 1‐year survival ROC, 2‐year survival ROC, 3‐year survival ROC and Kaplan–Meier (KM) survival of OC patients were also analysed by Sangerbox tool and KM Plotter database 23,24 . Furthermore, bioinformatics and text mining performed by Coremine Medical (http://www.coremine.com/medical/#search) was used to confirm whether DCTPP1 associated with OC and drug resistance 25,26…”
Section: Methodsmentioning
confidence: 99%
“…1‐year survival ROC, 2‐year survival ROC, 3‐year survival ROC and Kaplan–Meier (KM) survival of OC patients were also analysed by Sangerbox tool and KM Plotter database. 23 , 24 Furthermore, bioinformatics and text mining performed by Coremine Medical ( http://www.coremine.com/medical/#search ) was used to confirm whether DCTPP1 associated with OC and drug resistance. 25 , 26…”
Section: Methodsmentioning
confidence: 99%